Characterisation of titanium alloy feedstock for metal injection moulding using palm stearin binder system - Mohamad Nor, N. H.; Muhamad, Norhamidi; Jamaludin, Khairur Rijal; Ahmad, Sufizar; Ibrahim, Mohd. Halim Irwan (2009)
Metal injection moulding (MIM) is a cost-effective technique for producing small, complex, precision parts in high volume. Each step in MIM process plays a vital role in order to achieve high quality final product. To have a good understanding of the MIM process and successful in manufacturing, characterisation of the material feedstock is essential. This paper presents the characterization of MIM feedstock consisting titanium alloy (Ti-6Al-4V) powder mix with binder 60wt% of palm stearin and 40wt% polyethylene. The characterisation of Ti-6Al-4V alloy powder, binders and feedstock includes scanning electron micrograph (SEM), thermo gravimetric analysis (TGA), differential scanning calorimeter (DCS) and rheological test were established. Rheological results exhibited pseudoplastic or shear thinning flow behaviour, where its viscosity decreased with increasing shear rate. The feedstock viscosity also decreased with increasing temperature and was found to be suitable for moulding